Pushing boundaries in the measurement of language attitudes: Enhancing research practices with the L’ART Research Assistant app - Florian Breit; Marco Tamburelli; Ianto Gruffydd; Lissander Brasca (LingBaW)
The importance of methodological developments has recently been emphasised both in language attitude research specifically (Kircher & Zipp 2022), and across linguistics and the social sciences more broadly, where there has been a particular focus on replicability (Sönnig & Werner 2021; Kobrock & Roettger 2023). One aspect of this concerns the adoption of more open, consistent, and comparable implementations of method.